PENGETAHUAN DAN SIKAP BERHUBUNGAN DENGAN PERILAKU PEMERIKSAAN PAPSMEAR PADA GURU DI SELURUH SD MUHAMMADIYAH SAMARINDA KOTA SAMARINDA - Suri, Brigita Sheren Jessica; Ngo, Novia Fransiska; Nurul Hasanah (ITKES Wiyata Husada Samarinda, 2026)
Cervical cancer is the most common gynecological cancer in women worldwide. Most cases of cervical cancer are caused by the human papillomavirus (HPV). Cervical cancer begins in the cells lining the cervix, which is the lower part of the uterus that connects the uterine body to the vagina. There are methods for early detection of cervical cancer, including Pap smear examination. The aim of this research is to determine the relationship between knowledge and attitudes toward Pap smear examination and the behavior of undergoing Pap smear examination among teachers in all Muhammadiyah Elementary Schools in Samarinda City. The research design used in this study is observational analytic with a cross-sectional approach using a questionnaire as a research measurement tool. The sampling technique used is purposive sampling. The number of respondents in this study was 109 respondents. From the results of bivariate analysis using the chi-square test, a relationship was found between Pap smear knowledge and Pap smear behavior (p = 0.032) and Pap smear attitude and Pap smear behavior (p = 0.033). The conclusion of this study is that there is a relationship between knowledge and attitude with Pap smear behavior among teachers in all Muhammadiyah Elementary Schools in Samarinda City.